Effects of photoperiod and melatonin implants on feed intake in Atlantic salmon (Salmo salar L.) postsmolts - Maiolo, Silvia; Hansen, Tom Johnny; Parisi, Giuliana; Olsen, Rolf Erik (2016)
- High melatonin concentrations were expected to negatively affect Atlantic salmon appetite. Hence, individually kept Atlantic salmon postsmolts were subjected to continuous light (24:0, L:L) or natural daylight (12:12, L:D) and then given intraperitoneal implants of slow release melatonin in a 2 by 2 factorial design. Possible effects on food intake were monitored over three weeks. In addition, a plasma melatonin assessment test was run in parallel to monitor diurnal blood levels of melatonin through the trial. The surgical intervention was effective, leading to a 10x increase in mean melatonin levels when compared to control fish, but neither the implant nor the change in daylight had any significant effect on feed intake, at least in the short term.